2017
DOI: 10.1186/s12888-017-1447-3
|View full text |Cite
|
Sign up to set email alerts
|

Correct recognition and continuum belief of mental disorders in a nursing student population

Abstract: BackgroundThe current study aimed to explore the correct recognition of mental disorders across dementia, alcohol abuse, obsessive compulsive disorder (OCD), schizophrenia and depression, along with its correlates in a nursing student population. The belief in a continuum of symptoms from mental health to mental illness and its relationship with the non-identification of mental illness was also explored.MethodsFive hundred students from four nursing institutions in Singapore participated in this cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
2
18
2
Order By: Relevance
“…Regression analysis further substantiated this where compared with depression, medical students were significantly less likely to correctly recognise dementia (P=0.009) and schizophrenia (P<0.001). The latter corroborates findings of other local mental health literacy studies among the general population 12 and nursing students 25 in Singapore, which also found recognition was poorest for schizophrenia in comparison to the other four disorders. Mental health literacy studies elsewhere have also found schizophrenia to be more poorly recognised compared with depression.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regression analysis further substantiated this where compared with depression, medical students were significantly less likely to correctly recognise dementia (P=0.009) and schizophrenia (P<0.001). The latter corroborates findings of other local mental health literacy studies among the general population 12 and nursing students 25 in Singapore, which also found recognition was poorest for schizophrenia in comparison to the other four disorders. Mental health literacy studies elsewhere have also found schizophrenia to be more poorly recognised compared with depression.…”
Section: Discussionsupporting
confidence: 89%
“…In comparison to other local studies, recognition was considerably higher than that of the general Singapore population (43.7%) 12 and slightly higher than that of a nursing student sample (70.4%). 25 …”
Section: Discussionmentioning
confidence: 99%
“…(Reavley, McCann, & Jorm, 2012). This student population is better educated in mental health-related issues, not just in terms of education level but also because their chosen course is nursing/medicine, and therefore it is expected that they would be able to better recognize mental disorders, compared to the general population Seow et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Research investigating the relationship between obesity and mental health is increasingly considering mental health as a symptom continuum. The symptom continuum appreciates that individuals can experience one or more symptoms of mental illness without meeting diagnostic criteria for mental illness 18 19. Considering mental health as a continuum is associated with reduced stigma and improved attitudes towards mental health, highlighting the benefits of broadening the definition of mental health 19 20.…”
Section: Introductionmentioning
confidence: 99%